2012
DOI: 10.1590/s0004-282x2012000400015
|View full text |Cite
|
Sign up to set email alerts
|

The expanding spectrum of clinically-distinctive, immunotherapy-responsive autoimmune encephalopathies

Abstract: The autoimmune encephalopathies are a group of conditions that are associated with autoantibodies against surface neuronal proteins, which are likely to mediate the disease. They are established as a frequent cause of encephalitis. Characteristic clinical features in individual patients often allow the specificity of the underlying antibody to be confidently predicted. Antibodies against the VGKC-complex, mainly LGI1(leucine-rich glioma-inactivated 1), CASPR2 (contactin-associated protein 2), and contactin-2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…Approximately 31.70% of patients in this study rst showed FBDS, 67.50% EEG showed slow waves, focal discharges, temporal origins were more common, and even rare three-phase waves and the whole brain low voltage; 10.00% showed fast Increased activity; 10.00% normal EEG; 2.50% manifested as sharp wave delivery; it has been reported [9] 60% of patients with head MRI showed bilateral temporal lobe high signal, 40% is abnormal signal in one hippocampus or normal, our The report is generally consistent with the above.…”
Section: Discussionsupporting
confidence: 57%
“…Approximately 31.70% of patients in this study rst showed FBDS, 67.50% EEG showed slow waves, focal discharges, temporal origins were more common, and even rare three-phase waves and the whole brain low voltage; 10.00% showed fast Increased activity; 10.00% normal EEG; 2.50% manifested as sharp wave delivery; it has been reported [9] 60% of patients with head MRI showed bilateral temporal lobe high signal, 40% is abnormal signal in one hippocampus or normal, our The report is generally consistent with the above.…”
Section: Discussionsupporting
confidence: 57%
“…An accurate and early diagnosis is essential because both types of encephalitis may be fatal. Prognosis in both cases depends on the early institution of specific treatment, acyclovir in the case of HE, and immunotherapy or treatment of an underlying neoplasm in AE . Further knowledge on the clinical‐radiological differences and similarities between HE and AE may help in early clinical decisions.…”
Section: Introductionmentioning
confidence: 99%
“…3,6,7 These neuronal- or glial-surface–directed antibodies8 are detected by demonstration of antibody binding to the surface of human embryonic kidney cells that have been made to express the specific target (Fig 1A–C), to the surface of cultured live neurons (Fig 1D), and to fixed brain sections (see Fig 1E; these techniques have different merits and will be discussed later) 3,7,9. The clinical syndromes associated with neuroglial surface-directed antibodies (NGSAbs) frequently show a rapid onset, response to immunotherapies, good correlations between symptom course and antibody levels, and are less frequently associated with malignancies 2,7,10,11…”
mentioning
confidence: 99%